Analysis of Violations of Grice's Principles of Cooperation in the Mata Najwa Adu Kuat Program on Constitutional Affairs - Mauliyati Sari, Dewi; Suwadi, Suwadi; Rokhmawan, Tristan (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to analyze violations of Grice's principles of cooperation in the Mata Najwa program "Strong Fight on Constitutional Issues" and analyze the various responses that arise to violations of Grice's principles of cooperation using Grice's theory. Grice's theory of the principle of cooperation was chosen to analyze the Mata Najwa program because violations of the maxim of the principle of cooperation often occur in everyday communication, including on social media, one of which is the Mata Najwa program. It is felt that Grice's theory of cooperative principles can analyze how communication occurs in the Mata Najwa program. This research uses a qualitative descriptive method using content analysis methods. . The data analysis techniques used in this research are the listening technique and the observing technique. The listening technique was carried out by the researcher repeatedly listening to the video that had been downloaded in the form of the Mata Najwa program video with the theme Strong Fight on Constitutional Issues. Meanwhile, the note-taking technique is carried out by recording conversations which are indeed a data violation of the Grice cooperation principle contained in the Mata Najwa program. The data source in this research is language activities that occurred in the Mata Najwa program with the theme Strong Fight on Constitutional Issues on Thursday 28 March 2024. The results of this research found 70 utterances that violated Grice's principle of cooperation. Of the 70 speech data, there are 23 speeches that violate the maxim of quantity. For maximum quality there are 10 flowing utterances. Furthermore, for the maxim of relevance there are 15 intersecting statements. For the manner/implementation maxim, there are 22 utterances that violate the manner/implementation maxim. The response that emerged after the violation of Grice's principle of cooperation in the Mata Najwa Adu Strong Constitutional Issue program was that the interlocutor often gave a firm attitude, asked for clarification of the statements made, talked about other topics, and some even gave indifferent or indifferent responses.